Nonlinear Analytic Modeling for Novel Linear Variable Reluctance Motors - Aymen Lachheb; Jalel Khediri; Lilia El Amraoui (Advances in Science, Technology and Engineering Systems Journal, 2019)
In this paper, an analytical modeling is proposed to compute the static and dynamic characteristics of linear variable reluctance motors with taking account of the saturation and the non-linearity of the magnetic circuit. The proposed model is based on the Fourier series expression of the phase flux in which the variation of the linkage flux with phase current is defined by arc tangent function. Then, an analytical expression for the co-energy and electromagnetic forces are derivative. The effectiveness of the proposed method is proved in terms of accuracy by comparing the computed results obtained by the two dimensional finite elements method with analytic model. Subsequently, the proposed modeling approach is simple and provides accurate representation of linear variable reluctance motor, as confirmed by the compared results.
Keywords: Linear motor; Analytic modeling; Finite elements method; Fourier series